2021
DOI: 10.1007/s10340-021-01368-1
|View full text |Cite
|
Sign up to set email alerts
|

Potential host ranges of three Asian larval parasitoids of Drosophila suzukii

Abstract: Asobara japonica (Hymenoptera: Braconidae), Ganaspis brasiliensis and Leptopilina japonica (Hymenoptera: Figitidae) are Asian larval parasitoids of spotted wing drosophila, Drosophila suzukii (Diptera: Drosophilidae). This study evaluated these parasitoids’ capacity to attack and develop from 24 non-target drosophilid species. Results showed that all three parasitoids were able to parasitize host larvae of multiple non-target species in artificial diet; A. japonica developed from 19 tested host species, regard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 54 publications
2
32
0
Order By: Relevance
“…Only a single parasitoid emerged from D. melanogaster. This confirms our hypothesis and supports the results of previous laboratory choice and no-choice experiments performed in relatively small containers (Giorgini et al 2019;Girod et al 2018b;Biondi et al 2021;Seehausen et al 2020;Daane et al 2021).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Only a single parasitoid emerged from D. melanogaster. This confirms our hypothesis and supports the results of previous laboratory choice and no-choice experiments performed in relatively small containers (Giorgini et al 2019;Girod et al 2018b;Biondi et al 2021;Seehausen et al 2020;Daane et al 2021).…”
Section: Discussionsupporting
confidence: 92%
“…The risk of released parasitoids to also occasionally attack and kill native Drosophila species cannot be excluded, especially those that can be found in rotten or even injured fruits, such as D. melanogaster and D. simulans. But given the results of laboratory experiments (Giorgini et al 2019;Girod et al 2018b;Biondi et al 2021;Seehausen et al 2020;Daane et al 2021) and our field cage releases, parasitism of non-target species can be expected to be negligible and unlikely to have any significant ecological impact.…”
Section: Discussionmentioning
confidence: 95%
“…Research on potential biological control agents for D . suzukii illustrates that the introduced range is depauperate in natural enemies (Daane et al ., 2016, 2021; Kamiyama et al ., 2019), supporting the idea that populations on Hawaii might thrive due to enemy release rather than adaptation to their environment.…”
Section: Discussionmentioning
confidence: 99%
“…To determine the suitability of these parasitoids for classical biological control, studies of their biology and host range were conducted in quarantine facilities in Switzerland (Girod et al 2018b, c) and California (Wang et al 2018;Hougardy et al 2019;Wang et al 2019Wang et al , 2020Biondi et al 2021). Some populations of G. brasiliensis appear to be more specialized on D. suzukii, whereas other populations have broader host ranges (Girod et al 2018b;Seehausen et al 2020;Daane et al 2021). Nomano et al (2017) grouped G. brasiliensis into five "lineages" (G1-G5), hereafter referred to as "groups", based on molecular analyses and suggested that G1 material collected in Japan was host specific to D. suzukii.…”
Section: Introductionmentioning
confidence: 99%